Anxiety and depression in informal caregivers of dependent elderly people: an analytical study - Sarah Giulia Bandeira Felipe; Camila Evangelista de Sousa Oliveira; Cynthia Roberta Dias Torres Silva; Polyana Norberta Mendes; Khelyane Mesquita de Carvalho; Fernando Lopes Silva-Júnior; Maria do Livramento Fortes Figueiredo (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze the symptoms of anxiety and depression in informal caregivers of dependent elderly at home. Methods: Analytical, cross-sectional study conducted in the city of Teresina (PI), with informal caregivers of dependent elderly people. Data collection took place from November 2017 to February 2018, using a characterization form for the dependent elderly and their caregiver, Beck's Anxiety Inventory (BAI) and Beck's Depression Inventory (BDI). The forward linear regression model was used to identify the predictive variables of anxiety and depression. Results: It was found that 18.4% of caregivers had symptoms of depression; and 14%, moderate to severe anxiety. There was a correlation between anxiety and depression (p = 0.000). Conclusion: The findings of this study make it possible to assess anxiety and depression in caregivers of dependent elderly people, making it possible, through these parameters, to view the profile and care demands of this population.